A case report on COVID-19 associated multisystem inflammatory syndrome in children - Kumar, Sachin; Sharma, Deepak; Tongaria, Khushboo; Bansal, Naman (International Journal of Contemporary Pediatrics, 2021)
As severe acute respiratory syndrome coronavirus 2 continues to spread worldwide, there have been increasing reports from different parts of India during second wave of infection describing children and adolescents with COVID-19-associated multisystem inflammatory conditions. We describe clinical features and management in children with multisystem inflammatory syndrome children (MIS-C) from the Delhi metropolitan area, which had a high incidence of coronavirus disease 2019 (COVID-19). We report a similar case presenting with persisting fever, rashes, bulbar conjunctivitis, abdominal pain, decreased urine output and shock. Initial reports suggestive of high inflammatory markers, neutrophilic leukocytosis, high D-dimer and found to have COVID-19 IgG antibodies positive in high titre. Managed successfully in PICU with bolos fluids, intravenous antibiotics, steroids and anticoagulation.